2004
DOI: 10.1590/s0100-879x2004000400002
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and glutathione S-transferase (GSTM1/GSTT1) polymorphisms in a Brazilian population

Abstract: The distribution of polymorphisms related to glutathione S-transferases (GST) has been described in different populations, mainly for white individuals. We evaluated the distribution of GST mu (GSTM1) and theta (GSTT1) genotypes in 594 individuals, by multiplex PCRbased methods, using amplification of the exon 7 of CYP1A1 gene as an internal control. In São Paulo, 233 whites, 87 mulattos, and 137 blacks, all healthy blood-donor volunteers, were tested. In Bahia, where black and mulatto populations are more num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
2
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 30 publications
5
26
2
6
Order By: Relevance
“…The patients studied might have another genotype ancestry different from our data and the number of subjects was relatively small (n = 38). We also confirmed the pattern of cytogenetic abnormalities distribution was similar to larger series of patients and previously published in Brazil and elsewhere [8,9,14,15,[17][18][19].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The patients studied might have another genotype ancestry different from our data and the number of subjects was relatively small (n = 38). We also confirmed the pattern of cytogenetic abnormalities distribution was similar to larger series of patients and previously published in Brazil and elsewhere [8,9,14,15,[17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…There are no other studies reporting CYP1A1 * 3 frequency in AML patients [3][4][5][6][7][14][15][16][17][18]. Thus, by the multivariate analysis our data showed that CYP1A1 * 3 increases the risk of AML 4-fold.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The GSTM1 and GSTT1 null genotype frequencies for our Porto Alegre Afro-Brazilian sample were similar to those described for other Afro-Brazilian populations Rossini et al, 2002;Gattás et al, 2004) which themselves are similar to the frequencies described for other (non-Brazilian) Afro-descend populations (Harries et al, 1991, Bailey et al, 1998. These studies have also detected significant differences in the frequency of GSTM1 polymorphisms among Afro-Brazilians and Brazilians of European descent Rossini et al, 2002;Gattás et al, 2004).…”
supporting
confidence: 88%
“…Os dados da literatura são escassos em relação à contribuição de variáveis genéticas e a dieta no risco de câncer de cabeça e pescoço. É interessante ressaltar que variáveis específicas em nossa população podem contribuir para os resultados observados, como a frequência desses polimorfismos em diferentes grupos populacionais do Brasil 23 . Por outro lado, mesmo a alimentação pode ser extremamente variável em decorrência de fatores ambientais e culturais.…”
Section: Discussionunclassified